Optimization of constellation jettisoning regards to short term collision risks. (April 2018) - Handschuh, D.-DA.-A.; Bourgeois, E.
Abstract: The space debris problematic is directly linked to the in-orbit collision risk between artificial satellites. With the increase of the space constellation projects, a multiplication of multi-payload launches should occur. In the specific cases where many satellites are injected into orbit with the same launcher upper stage, all these objects will be placed on similar orbits, very close one from each other, at a specific moment where their control capabilities will be very limited. Under this hypothesis, it is up to the launcher operator to ensure that the simultaneous in-orbit injection is safe enough to guarantee the non-collision risk between all the objects under a ballistic hypothesis eventually considering appropriate uncertainties. The purpose of the present study is to find optimized safe separation conditions to limit the in-orbit collision risk following the injection of many objects on very close orbits in a short-delay mission. Highlights: Increase of multi-payload launches involves specific collision problematics. Launch operator has to ensure safety between launcher's co-passengers. Optimization of separation conditions to limit in-orbit collision risk is proposed. Good practices to analyze a deployment strategy is proposed.